PENGARUH PENGGUNAAN TEKNOLOGI PEMBELAJARAN INTERAKTIF TERHADAP PENINGKATAN KEMAMPUAN BAHASA INGGRIS MAHASISWA PRODI INFORMATIKA DI ITB AAS INDONESIA - Muliasari, Dewi; Efendi, Tino Feri (JURNAL ILMIAH EDUNOMIKA, 2024)
This research investigates the impact of interactive learning technology on the English language proficiency of Informatics students at ITB AAS Indonesia. A quasi-experimental design was employed, involving an experimental group that utilized interactive learning technology and a control group that received conventional instruction. The findings reveal a significant improvement in the English language skills of the experimental group, highlighting the effectiveness of interactive technology in enhancing listening, speaking, reading, and writing abilities. Additionally, the study demonstrates that interactive learning tools positively influence students' motivation and engagement, aligning with theories such as the Cognitive Theory of Multimedia Learning (CTML), Self-Determination Theory (SDT), and Cognitive Load Theory (CLT). The research underscores the potential of integrating interactive technology into non-language focused programs, providing practical insights for educators and institutions seeking to innovate English language instruction in higher education. Keywords : Interactive learning technology, English language proficiency, Informatics students, CTML, Self-Determination Theory (SDT), Cognitive Load Theory (CLT), higher education